Late home ownership and social re-stratification. Issue 2 (3rd April 2018) - Forrest, Ray; Hirayama, Yosuke
Abstract: Home ownership was a significant element of social change in the post-war, mature, capitalist economies such as the United Kingdom, United States and Japan. This growth of individual home ownership occurred, however, within a particular demographic, economic, social and political context. This distinctive set of conditions include the atomized, nuclear family; suburbanization; high growth; the conventional mortgage market and a young, working population. These conditions have changed and coalesce in the constitution of what we refer to as 'late home ownership'. The paper conceives of contrasts between 'real estate families' or 'accumulating families' which maintain or further accumulate valuable multiple property assets over generations; 'dissipating families' which are forced to deploy and diminish their property assets accumulated in the exceptional era; and propertyless 'perpetual renter families'. It is argued that these emergent divisions are pivotal in understanding new forms of social re-stratification in which the patterns of ownership of residential property, the income flows from residential property investment, a changed demographics and intergenerational dynamics are key drivers.